Barriers for developing building with low embodied energy multi criteria decision making approach - Haruna, Abdulrahman; Shafiq, Nasir; Montasir, O. A.; Haruna, Sani (International Journal of Engineering and Technology, 2018)
Design, construction management and procurement play a vital role in Building projects. Subsequent design decision, construction man-agement activities and procurement policies tend to become barriers to sustainable construction by impacting negatively toward the environment. This paper pinpoints the barriers faced in embodied energy minimization by professionals in the Malaysia construction industry. Construction expert opinion was collected through design questionnaire survey which was scale according to saaty’s with (1) equal importance to (9) extreme importance. The returned questionnaires were then inputted into the multi criteria decision making tools. Ana-lytical network process (ANP) was used to determine which barrier among design, construction management and procurement has sig-nificant impact on the sustainability of building project. The barriers with most significant influence in the construction industry regard-ing embodied energy were found to be high level of wastage (CM01), Non-consideration of embodied impacts in assessment of offers (P01) and over specification in design due to additional factors of safety (D02).